The contribution of pro-poor growth programmes to poverty reduction in Rwanda : a case study of the Girinka Programme in rural Rwanda - Rugema, Michelle (Department of Sociology, 2015)
This study investigates the contribution of the Girinka Programme, a pro-poor growth programme in Rwanda, to poverty reduction. Recent studies have placed increasing emphasis on the contribution of pro-poor growth to poverty reduction and have argued that pro-poor growth has the potential to reduce poverty more effectively than economic growth. Poverty, for this study, is measured based on the following indicators of poverty derived from the United Nations (1998) definition of poverty: nutrition, access to health care services, access to water, education, and access to credit. Income or the lack thereof, is not the sole determinant of poverty, and is not “the sum total of human life” (United Nations Development Programme, 1990), therefore relying solely on quantitative measurements of poverty that are based on income can paint an incomplete picture of the reality on the ground. Therefore, since poverty is multidimensional, this study uses a multidimensional approach to its analysis and goes beyond the quantitative aspects of poverty. Qualitative research methods were used for this study, and fieldwork was conducted in Kayonza District, located in the Eastern Province of Rwanda. In-depth interviews were held with beneficiaries and prospective beneficiaries of the Girinka Programme in order to determine the programme’s contribution to a meaningful reduction in poverty. In addition, interviews were held with Girinka local and national programme officials. Secondary data in the form of programme documents was also collected, reviewed and analysed.